Aerodynamics of ceramic regular sedimentation for heat and mass transfer apparatuses of environmental protection - Pushnov, Aleksandr; Sakalauskas, Algirdas (Journal of Environmental Engineering and Landscape Management, 2008)
A new efficient ceramic regular sedimentation for heat and mass transfer in apparatuses of environmental protection is proposed. A new sedimentation realization with isotropic properties of a structure is offered. The aerodynamic test results of the new sedimentation are shown. The paper describes a laboratory test facility designed for conducting aerodynamic investigation of cooling tower sedimentation. Measured parameters, data processing techniques and examples of the results obtained are discussed. The tested sedimentation is a porous layer of ceramic foam manufactured by special technology. Article in Russian. Keraminių reguliarių antgalių aerodinamika šilumos ir masės pernašos procesams aplinkos apsaugos įrenginiuose vykdyti Santrauka. Siūloma nauja keraminių reguliarių antgalių dinamika šilumos ir masės pernašos procesams aplinkos apsaugos įrenginiuose vykdyti. Siūlomas antgalis leis realizuoti poringojo sluoksnio izotopinę struktūrą. Pateikti naujo antgalio aerodinaminių bandymų rezultatai. Reikšminiai žodžiai: antgalis, šilumos ir masės pernaša, aerodinaminis bandymas. Аэродинамика керамических регулярных насадок для тепломассообменных процессов в аппаратах защиты окружающей среды Резюме. Предложена новая эффективная керамическая регулярная насадка для осуществления процессов тепло- и массообмена в аппаратах газоочистки. Предлагаемая насадка позволяет реализовать изотропную структуру зернистого слоя. Приведены результаты аэродинамических испытаний новой насадки. Ключевые слова: насадка, тепло- и массообмен, аэродинамические испытания. First Published Online: 14 Oct 2010